Association of nurse work environment and safety climate on patient mortality: A cross-sectional study. (September 2017) - Olds, Danielle M.; Aiken, Linda H.; Cimiotti, Jeannie P.; Lake, Eileen T.
Abstract: Background: There are two largely distinct research literatures on the association of the nurse work environment and the safety climate on patient outcomes. Objective: To determine whether hospital safety climate and work environment make comparable or distinct contributions to patient mortality. Design: Cross-sectional secondary analysis of linked datasets of Registered Nurse survey responses, adult acute care discharge records, and hospital characteristics. Setting: Acute care hospitals in California, Florida, New Jersey, and Pennsylvania. Participants: The sample included 600 hospitals linked to 27, 009 nurse survey respondents and 852, 974 surgical patients. Methods: Nurse survey data included assessments of the nurse work environment and hospital safety climate. The outcome of interest was in-hospital mortality. Data analyses included descriptive statistics and multivariate random intercept logistic regression. Results: In a fully adjusted model, a one standard deviation increase in work environment score was associated with an 8.1% decrease in the odds of mortality (OR 0.919, p < 0.001). A one-standard deviation increase in safety climate score was similarly associated with a 7.7% decrease in the odds of mortality (OR 0.923, p < 0.001). However, when work environment and safety climate were modeled together, the effect of the work environment remained significant, while safety climate became a non-significant predictor of mortality odds (OR 0.940, p = 0.035 vs. OR 0.971, p = 0.316). Conclusions: We found that safety climate perception is not predictive of patient mortality beyond the effect of the nurse work environment. To advance hospital safety and quality and improve patient outcomes, organizational interventions should be directed toward improving nurse work environments.